Mad Loves : Women and Music in Offenbach's Les Contes d'Hoffmann - Hadlock, Heather (Book collections on Project MUSE., 2000)
"In an exploration of Jacques Offenbach's final masterpiece, Heather Hadlock shows how Les Contes d'Hoffmann summed up not only the composer's career but also a century of Romantic culture. A strange fusion of irony and profundity, frivolity and nightmare, the opera unfolds as a series of dreamlike episodes, peopled by such archetypes as the Poet, the Beautiful Dying Girl, the Automaton, the Courtesan, and the Mesmerist. Hadlock shows how these episodes comprise a collective unconscious. Her analyses touch on topics ranging from the self-reflexive style of the protagonist and the music, to parallels between nineteenth-century discourses of theater and medical science, to fascination with the hysterical female subject."--Jacket